2017
DOI: 10.1038/s41598-017-00866-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ion migration and interfacial degradation of CH3NH3PbI3 perovskite solar cells under thermal conditions

Abstract: Organic-inorganic hybrid perovskite solar cells (PSCs) have been extensively studied because of their outstanding performance: a power conversion efficiency exceeding 22% has been achieved. The most commonly used PSCs consist of CH3NH3PbI3 (MAPbI3) with a hole-selective contact, such as 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9-spiro-bifluorene (spiro-OMeTAD), for collecting holes. From the perspective of long-term operation of solar cells, the cell performance and constituent layers (MAPbI3, spiro-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 49 publications
0
97
0
1
Order By: Relevance
“…Moreover, it is also not rigorous to only measure one crystal plane to identify the phase, because the decomposed materials have approximate interplanar spacings with intrinsic perovskite. As shown in Figures 4(E)‐(H), 19,22,24,33 we completely cannot identify whether these materials are MAPbI 3 perovskite, PbI 2 , Pb or other intermediates based on one crystal plane. It generally seems to happen when the crystal is oriented in a way where lines are formed in the image due to tilting.…”
Section: Ignoring the Proofreading Of Decomposition Productmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, it is also not rigorous to only measure one crystal plane to identify the phase, because the decomposed materials have approximate interplanar spacings with intrinsic perovskite. As shown in Figures 4(E)‐(H), 19,22,24,33 we completely cannot identify whether these materials are MAPbI 3 perovskite, PbI 2 , Pb or other intermediates based on one crystal plane. It generally seems to happen when the crystal is oriented in a way where lines are formed in the image due to tilting.…”
Section: Ignoring the Proofreading Of Decomposition Productmentioning
confidence: 94%
“…The widely existed misidentifications have negatively influenced the development of perovskite research field, such as structural determination, material growth, phase transition, heterostructure and so on 6,15–45 . Although the mistakes are being taken seriously, 14,46 analysing the causes of misidentifications, and proposing a solid method of phase identification for electron beam‐sensitive materials is still highly urgent.…”
Section: Introductionmentioning
confidence: 99%
“…It was early noted that even in the dark, PSCs shows relatively large capacitances (~50 µF cm -2 ) at low frequencies as compared with geometrical capacitance, irrespective of the perovskite bulk thickness (Almora et al, 2015). This fact indicated that interfaces between the absorbing semiconductor and contacting layers would be behind these uncommon capacitive experimental trends (Bergmann et al, 2016;Carrillo et al, 2016;Kim et al, 2017). Simultaneously, it was reported a hysteretic effect of the J-V curve under operation.…”
Section: Introductionmentioning
confidence: 98%
“…Chemical etching, also called plasma ashing, may remove organic matter and enlarge the size of nano-sized voids in spiro-OMeTAD HTL. The diffused negative ions from perovskite surface, such as I − into the voids in spiro-OMeTAD HTL may prevent oxidation of spiro-OMeTAD, and degrade the electric properties [30,31], which led to the “deterioration and recovery” behavior of spiro-OMeTAD HTL exposed to O 2 plasma.…”
Section: Resultsmentioning
confidence: 99%